ON THE STABILITY ANALYSIS OF PLATES AND SHELLS USING A QUADRILATERAL, 16-DEGREES OF FREEDOM PLAT SHELL ELEMENT DKQ16 - 郑长良 李丽华 钟万勰 (Applied mathematics and mechanics, 2004)
The linear buckling problems of plates and shells were analysed using a recently developped quadrilateral, 16-degrees of freedom flat shell element ( called DKQ16 ). The geometrical stiffness matrix was established. Comparison of the numerical results for several typical problems shows that the DKQ16 element has a very good precision for the linear buckling problems of plates and shells.